Towards Adapting a Content Orchestrator to a Different GameGenre: Generating Levels, Rules, and Narrative for Diverse Player Profiles from a Top-down Adventure to a 2D Platformer - Teoi, Tyago Yuji; Pereira, Leonardo Tórtoro; Toledo, Claudio Fabiano Motta (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
Procedural Content Generation for multiple game content facets is a challenge for the game industry and academia. A content orchestrator is a software that can manage different procedural content generators, mixing their outputs while maintaining coherence and feasibility. We adapted a content orchestrator, originally meant for a top-down adventure game, to a 2D platformer. Both versions procedurally generate Levels, Rules, and Narrative, while adapting to distinct player profiles. A pre-test questionnaire is used to evaluate the player profile, and a post-test questionnaire is used to evaluate the game prototype we developed for this experimental purpose and the procedurally generated content. Results show the game was fun, challenging, interesting to explore, and with a moderate difficulty. Although with a limited sample, our results indicate the system was able to target content based on profiles. Therefore, this is a first step into understanding how a content orchestrator can be adapted to different game genres.